Developmental morphological characteristics of sympathetic ganglia in premature infants - K. V. Dashichev; N. V. Olendar; E. P. Sitnikova; T. L. Uspenskaya; O. V. Kulibina (LLC "Diagnostics and Vaccines", 2024)
The results of morphological and clinical-functional studies of the central and peripheral departments of the sympathoadrenal systems of premature newborns are presented. According to the morphometry of deceased newborns, along with pronounced immaturity, a stably reduced number of neurocytes of the cervical-thoracic (stellate) ganglia of the sympathetic chain of premature infants was found, which can limit the level of their motor activity for a long time. Low activity of sub-cortical sympathoadrenal systems, due to antenatal inhibition under the influence of a number of factors, may be the cause of the syndrome of general depression of the central nervous system in premature infants.